Positive interaction of trembesi (Samanea saman) and arbuscular mycorrhizae fungi in Pb stabilization of gold-mine tailing media - LULUK SETYANINGSIH; FILDZAH AISYAH RAMADHANI; ZAINAL MUTTAQIN; MAMAY MASLAHAT (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Setyaningsih L, Ramadhani FA, Muttaqin Z, Maslahat M. 2024. Positive interaction of trembesi (Samanea saman) and arbuscular mycorrhizae fungi in Pb stabilization of gold-mine tailing media. Biodiversitas 25: 379-385. This experiment aimed to determine the ability of trembesi (Samanea saman Merr.) seedlings inoculated with AMF (Glomus manihotis) to reduce Pb from gold mine tailings media. Therefore, using plants and Arbuscular Mycorrhizae Fungi (AMF) is an alternative choice that can be considered to support a phytoremediation program to reduce Pb contamination in tailing areas. The experiment was conducted using a completely randomized design in a greenhouse with two factors, i.e., with and without AMF, and four different Pb treatments (0, 0.5, 1, and 1.5 mM). AMF-inoculated seedlings were grown on tailings media and exposed to Pb in different concentrations for 5 weeks. The results showed that the seedlings were still able to grow on the media with Pb up to 1.5 mM with a tolerance index of 91.6%. AMF induced the plant to accumulate Pb dramatically higher, even though this absorption tended to reduce plant biomass. Root tissue stored significantly higher Pb than stem and leaf tissue, with an average concentration was 526.29 mg/kg in the roots of mycorrhizal seedlings. The bioaccumulation level of Pb in mycorrhizal seedlings was significantly higher. The value of the transport factor was below 1, indicating that S. saman seedlings carried out the phytostabilization. The interaction of AMF with S. saman has a big potential to be applied in efforts to remediate Pb in tailings.